Duration of the efficacy of omalizumab after treatment discontinuation in 'real life' severe asthma. Issue 8 (27th October 2017) - Vennera, Maria del Carmen; Sabadell, Carlos; Picado, Cesar
Abstract : Efficacy of omalizumab in severe asthma is well documented; however, the optimal duration of the treatment remains unclear. In an open prospective study, we sought to assess the persistence of response in subjects withdrawing from omalizumab treatment. We evaluated 49 patients who voluntarily accepted to discontinue omalizumab treatment after 6 years of therapy. Asthma relapse was defined as any severe asthma exacerbation associated with loss of asthma control. Twelve patients relapsed in the first year of follow-up, and 7 within 13 and 48 months. These results suggest that the effects of 6 years of omalizumab may persist after discontinuation of therapy in 60% of patients for at least 4 years.